The Preparation of Financial Statements Based on Psak No. 1 Concerning Presentation of Financial Reports At PT DSM Sura-baya - Nikma Yucha; Mitha Otik Wiraswati; Desy Lindawati (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2022)
Statement of Financial Accounting Standards is an instruction from accounting procedures which include the processing, recognition, preparation and presentation of financial statements. Financial reports according to PSAK 1 consist of balance reports, profit and loss reports, reports on changes in capital, cash flow reports, and notes to financial reports. From the initial research it was found that in the December 2021 period the company only presented balance reports, profit/loss reports, reports on changes in capital and cash flow reports. This study aims to identify and analyze the preparation of the financial statements of PT. DSM complies with PSAK No. 1. The method used for this research is descriptive qualitative. This method uses 3 processes, namely reducing, presenting and concluding. The data collection technique used is the method of observation, interviews, documentation. This study evaluates the financial statements of PT. DSM, the first thing to do is to check the format and standards used by the company, calculate the suitability of PT DSM's financial statements with PSAK No. 1 and present financial reports according to PSAK No. 1. Based on this research, it can be concluded that the financial statements prepared by PT. Most of the DSM have fulfilled the characteristics of PSAK No. 1, but there are some that have not been fulfilled, such as not making an explicit statement regarding compliance with applicable accounting standards, where this statement can be poured into the notes to the financial statements and has not presented comparative information. In addition, PT DSM has presented good financial reports even though the conformity level of the balance sheet is 35.29% and the level of non-conformity is 64.71% and there are several adjustments to the mention of items in the balance sheet, while for changes in profit/loss reports to profit/income statements. comprehensive loss as well as additions for making notes to the financial statements.